Serangan Militer Israel di Jalur Gaza: Pertanggung jawaban Pidana Berdasarkan Statuta Roma Mahkamah Pidana Internasional - Veny Pasuria Marpaung; Gladi Agustina Sihombing; Haliza Maulida; Ahmad Ridho; Budi Ardianto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
War conflict is something that is difficult for countries to avoid. For example, conflicts between Israel and Palestine occur repeatedly, but the realization of international accountability is not yet in accordance with existing regulations. The events that resulted in casualties in the war must be held accountable by Israel as a State, as well as the individuals involved. As a result of these actions, the perpetrators of war crimes must be held accountable under international law. The research method used is normative juridical research, namely by using library materials, by studying and examining the regulations governing international criminal law, both regulations from the Indonesian government and the constitution issued by the Rome Statute. Based on the results of research and discussion, it can be seen that the mechanism for enforcing international criminal law based on the 1998 Rome Statute is carried out through several stages, namely submission of a case by the state party, investigation and prosecution, trial, decision making, finally appeal and review.